Systemic Juvenile idiopathic arthritis in child complicated by amyloidosis with secondary nephrotic syndrome - Shah, Syed Sajid Hussain; Aalia, Bibi (Journal of Gandhara Medical and Dental Science, 2024)
A 7 years old girl diagnosed as case of juvenile idiopathic arthritis since the age of 1.5 years, generalized onset with systemic presentation is complicated by secondary nephrotic syndrome. Renal biopsy showing amyloidosis. Patient has severe disease course being complicated by sever flare ups of disease symptoms and body swelling. Since onset of disease patient got NSAIDs, methotrexate, steroids, anti TNF inhibitors with no or partial response. After diagnosis with secondary nephrotic syndrome due to secondary amyloidosis patient is started on intravenous tocilizumab. There is improvement of patient symptoms.